Differential Oscillatory EEG between Attention Deficit Hyperactivity Disorder Subtypes and Typically Developing Adolescents - Mazaheri, Ali (2013)
BACKGROUND: A neurobiological-based classification of Attention Deficit Hyperactivity Disorder (ADHD) subtypes has thus far remained elusive. The aim of this study was to use oscillatory changes in the electroencephalogram (EEG) related to informative cue processing, motor preparation, and top-down control to investigate neurophysiological differences between typically developing (TD) adolescents, and those diagnosed with predominantly inattentive (IA), or combined (associated with symptoms of inattention, as well as impulsivity/hyperactivity; CB) subtypes of ADHD. METHODS: EEG was recorded from 57 rigorously screened adolescents (aged 12 to17 years; 23 TD, 17 IA and 17 CB), while they performed a cued flanker task. We examined the oscillatory changes in theta (3–5 Hz), alpha (8–12 Hz) and beta (22–25 Hz) EEG bands following cues that informed participants with which hand they would subsequently be required to respond. RESULTS: Relative to TD adolescents the IA group showed significantly less post-cue alpha suppression, suggesting diminished processing of the cue in the visual cortex, whereas the CB group showed significantly less beta suppression at the electrode contralateral to the cued response hand, suggesting poor motor planning. Finally, both ADHD subtypes showed weak functional connectivity between frontal theta and posterior alpha, suggesting common top-down control impairment. CONCLUSIONS: We found both distinct and common task-related neurophysiological impairments in ADHD subtypes. Our results suggest that task-induced changes in EEG oscillations provide an objective measure, which in conjunction with other sources of information might help distinguish between ADHD subtypes and therefore aid in diagnoses and evaluation of treatment.